Application of Modified Ghadle-Munot Method in Applied Mathematics Learning through Chocolate Production Case Study at CV. Putra Mataram Sedalu - Firdaus, Ahmad; Busrah, Zulfiqar; Azmidar, Azmidar; Buhaerah, Buhaerah (JTMT: Journal Tadris Matematika, 2025)
Applied mathematics plays an important role in solving real-world problems, including in the agricultural product processing industry. This study aims to apply the Modified Ghadle-Munot method to solve employee assignment problems in a private company operating in chocolate production and to connect its implementation with applied mathematics learning. The core issue addressed is the imbalance between the number of employees and the number of production stages, which creates an unbalanced assignment problem. This study uses an applied quantitative research approach with assignment optimization as the main variable. Data were collected through interviews and documentation related to the production process and employee task distribution. The results showed that the Modified Ghadle-Munot method was able to reduce the total work time from an initial average of 970 minutes to 660 minutes. The application of this algorithm not only improves operational efficiency but also carries educational value. It can serve as a contextual case study in teaching applied mathematics, particularly in linear programming and optimization. Therefore, this research contributes both to practical problem-solving in small-scale industry settings and to strengthening real-world, problem-based learning in mathematics education.